A case report Adenoid Ameloblastoma as a Trap for Inexperienced Pathologists: A Case Report - Mashhadiabbas, Fatemeh; Gholami Toghchi, Sanaz; Kashefi Baher, Mohammadreza; Arefi fard, Hamidreza (Journal of Dental School, 2024)
Objectives Ameloblastoma is the second most frequent type of odontogenic tumors. They are thought to be formed by epithelium of ectodermal origin, Histopathologically, ameloblastoma has plexiform, follicular, acanthomatous, desmoplastic, granular cell, and basal cell subtypes. Adenoid ameloblastoma, also called dentinal adenoid ameloblastoma, is a rare odontogenic tumor. About 40 cases have been reported, with the highest incidence in the fourteenth year of life (age range:25-52 years), indicating a small female population and a similar population for ameloblastoma. The differential diagnosis includes odontogenic lesions such as calcifying odontogenic cyst, calcified epithelial odontogenic tumor, ameloblastoma and adenomatoid odontogenic tumor (AOT). Histopathological results show that odontogenic epithelial tumors consist of nests, islands, cords, anastomotic chains and large areas of epithelium, ameloblast-like cells in the periphery, stellate reticulum-like cells in the space and cystic/microcystic patterns, acanthomatous changes and ductal patterns similar to AOT. Case The aim of this report was to present a unique case of adenoid ameloblastoma affecting the right side of mandible in a 47 y.o woman which had a previous pathology diagnosis of adenoid cystic carcinoma for this lesion in her medical history. Conclusion Such rare cases of adenoid ameloblastoma can pose challenges in the initial diagnosis and treatment.